Pike, Wisconsin : Unstable - Book 3 - Ivy, Alexandra (New York, NY : Zebra Books, Kensington Publishing Corporation, 2022)
"In New York Times bestselling author Alexandra Ivys third bone-chilling romantic thriller set in Pike, Wisconsin, a small town with more secrets than residents, a cold case expert and her sheriff ex-husband reunite to solve a cold case when footage of a bound and gagged girl is discovered on a mysterious old VHS tape."--
A dead man in a cemetery isnt news--unless hes found on top of a grave, with a bullet through his head. The body belongs to Jude Henley, who was supposed to be buried below. Instead, the grave contains the remains of Staci Gale, thought to have run away nearly three decades ago. Then an old VCR tape arrives at the sheriff station, showing Staci before her death--bound and terrified--with a note, claiming to be from the killers apprentice... Rachel Fishers job in cold case files has brought her back to Pike, Wisconsin--where shell be working alongside her ex-husband, Zac Evans. As Pikes interim sheriff, Zac expected a low-key assignment. Instead, he and Rachel are racing to solve serial murders from decades past while a new monster goads them with a chilling promise. Every week therell be another old tape--and a fresh victim... In this small town a killer walks--twisted, ruthless, determined to continue his masters work. And unless Rachel and Zac can find a way to get ahead of him, the nightmare will never end.
Keywords: Serial murders -- Fiction; Murder -- Investigation; Fiction; Cold cases (Criminal investigation) -- Fiction; Video recordings -- Fiction; Divorced people -- Fiction; Wisconsin -- Fiction; Romantic suspense fiction; Thrillers (Fiction); Romance fiction